Breast cancer in women with primary biliary cirrhosis. Issue 6509 (7th December 1985) - Goudie, B M; Burt, A D; Boyle, P; Macfarlane, G; Birnie, G G; Mills, P R; Gillis, C R; MacSween, R N; Watkinson, G
Abstract : The occurrence of extrahepatic malignancy was studied in 195 unselected patients who satisfied predetermined biochemical, immunological, and histological criteria for the diagnosis of primary biliary cirrhosis. The incidence of breast cancer in women with primary biliary cirrhosis was found to be significantly higher than in an age and sex matched control population from the same well defined geographical area (p less than 0.0015). The association of breast cancer and primary biliary cirrhosis remains unexplained, though diminished immunological surveillance, fat soluble vitamin deficiency, or endocrine dysfunction may play a part.